2017
DOI: 10.1177/0731948717690114
|View full text |Cite
|
Sign up to set email alerts
|

When a Parent of a Student With a Learning Disability Is Also an Educator in the Same School District: A Heuristic Case Study

Abstract: Advocating for the educational rights of a child with a disability can be intimidating for parents, even for those who are well versed in the language and protocols of the special education system. Securing the rights of a historically marginalized group has indeed been a challenging task and required much effort on the part of parents, educators, lawyers, and policy makers. Even so, parents of children with disabilities have continued to encounter barriers in becoming equal members in the educational planning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…One possible rationale for the differences, consistent with Haley et al (2018), is that a significant number of those dis/abled respondents employed in the field may have worked in or near the Districts providing services to their child or children. Dis/abled Fig.…”
Section: Compliance With Idea 2004 Requirementsmentioning
confidence: 79%
“…One possible rationale for the differences, consistent with Haley et al (2018), is that a significant number of those dis/abled respondents employed in the field may have worked in or near the Districts providing services to their child or children. Dis/abled Fig.…”
Section: Compliance With Idea 2004 Requirementsmentioning
confidence: 79%
“…Parents need to advocate for the services their children need but may feel that asking for too much or too often will make them "pushy parents" (Beauvais, 2017;Bibby et al, 2017). Haley, Allsopp, and Hoppey (2018) found that even when a parent was a teacher at their child's school, there were barriers to their inclusion as full team members in their child's educational decision-making team. This parent cited a "learning curve to special education" (p. 26) along with loyalty and job security issues if she complained or did not do what the school thought was right.…”
Section: Barriers To Parental Involvementmentioning
confidence: 99%
“…The assumption is that using family-centered practices will lead to increased parental involvement and that teachers who have been trained in family-centered practices will better establish family-school partnerships and include parents in children's education. However, family-centered practices may not be the norm in public PreK-12 schools (Allen & White-Smith, 2018; Cavendish & Connor, 2018; Haley et al, 2018;Lechuga-Peña & Brisson, 2018;Pemberton & Miller, 2015;Valle, 2018).…”
Section: Family-centered Practices To Foster School-family Partnershipsmentioning
confidence: 99%
“…or with others to devise ways to reach specific goals for their child with a disability (Haley, Allsopp, & Hoppey, 2018;Harnett, Tierney, & Guerin, 2009). Empowerment involves special educators and parents in the creation of individualized, resource-oriented solutions centered on a child's needs.…”
Section: Parental Empowerment Definedmentioning
confidence: 99%
“…This relationship in the special education environment focuses on parent and child competencies versus deficits, strengths versus weaknesses, capabilities versus risks, and hope versus hopelessness. In short, empowerment is the facilitation of participation focused on attainable goals and parents’ ability to work alone or with others to devise ways to reach specific goals for their child with a disability (Haley, Allsopp, & Hoppey, 2018; Harnett, Tierney, & Guerin, 2009). Empowerment involves special educators and parents in the creation of individualized, resource-oriented solutions centered on a child’s needs.…”
Section: Parental Empowerment Definedmentioning
confidence: 99%